Criminological and Administrative Law Perspectives on the Potential Abuse of Authority in Regional Government Procurement of Goods and Services - Muhamad Ali Sariati; Akhmad Munawar; Salimna Maulida Azzahra; Sudiyono S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Procurement of Goods and Services (PBJ) within local governments is a vital instrument of development that is very vulnerable to abuse of authority practices and corruption crimes. This study aims to examine the limitations of the authority of local government apparatus from the perspective of State Administrative Law and analyze the triggering factors for these deviations using a criminological approach. This research is normative law using a statutory approach and a conceptual approach. The results of the study show that, administratively, the discretion in PBJ must be strictly limited by the General Principles of Good Governance (AAUPB) to prevent the occurrence of detournement de pouvoir, which is supported by the optimization of preventive supervision through probity audits by the Government Internal Supervision Apparatus (APIP). Meanwhile, criminological reviews classify these crimes as white-collar crimes which are analyzed using the Fraud Triangle theory. Corruption of the regional PBJ is triggered by local political pressure, gaps in supervision (opportunities), and normalization of corrupt behavior (rationalization).